معاينة وإثبات الغش الجبائي: Previewing and Proving Fiscal Fraud - بخدة عواد (Journal of North African Economies, 2025)
Fiscal Fraud is a dangerous economic crime that causes weak fraud collection and lack of revenues in exchange for the terrible increase in expenses, which ultimately leads to an imbalance in the public budget and consequently the inability to maintain political and social balances especially when petroleum revenues are no longer sufficient to cover expenditures. This requires concerted efforts to fight tax fraud in its various forms. Previewing and proving the facts of this crime can be the basic building block for the success of efforts aimed at fighting the multiple appearances of fiscal fraud. Preview and proof procedures in this type of crime are distinguished by their peculiarities, whether with regard to the persons qualified to carry out these procedures or in terms of means and legal authentic according to our personal opinion, to more development, especially with the increasing and complexity of fiscal fraud cases.